Beliefs and views of caregivers of older women living with dementia about end of life, feeding and dysphagia (Research, Society and Development, 2022)
In Brazil, end-of-life’ decisions of elderly people with dementia are commonly made by their caregivers, because they usually do not have advance directives. One of the most difficult and conflicted decision is on feeding options (oral versus gastrostomy), maybe due the caregiver’s beliefs and views, that are, however, rarely studied. This qualitative study aimed to analyze beliefs and views of five demented elderly people’s caregivers regarding end-of-life, dementia, feeding, swallowing and dysphagia in a public home care service. The researchers interviewed these caregivers; they audio-recorded and transcribed the interviews, and the content analysis was used for data analysis and interpretation. The caregivers associated eating and drinking to survival and caring. Caregivers of elderly women who received oral feeding mentioned feelings of gratitude and well-being; the caregivers of the elderly woman with tube feeding highlighted feelings such as sadness, displeasure and concern on nutritional aspects. All the caregivers identified difficulty in eating and/or swallowing of their cared ones, and they said that dysphagia had negative impact on both lives (cared one and caregivers), associating dysphagia as a marker of the end of life.